Dearomative photocatalytic construction of bridged 1,3-diazepanes - Leitch, JA; Rogova, T; Duarte Gonzalez, FJ; Dixon, DJ (Wiley, 2020)
The construction of diverse sp3 -rich skeletal ring systems is of importance to drug discovery programmes and natural product synthesis. Herein, we report the photocatalytic construction of 2,7-diazabicyclo[3.2.1]octanes (bridged 1,3-diazepanes) via a reductive diversion of the Minisci reaction. The fused tricyclic product is proposed to form via radical addition to the C4 position of 4-substituted quinoline substrates, with subsequent Hantzsch ester-promoted reduction to a dihydropyridine intermediate which undergoes in situ two-electron ring closure to form the bridged diazepane architecture. A wide scope of N-arylimine and quinoline derivatives was demonstrated and good efficiency was observed in the construction of sterically congested all-carbon quaternary centers. Computational and experimental mechanistic studies provided insights into the reaction mechanism and observed regioselectivity/diastereoselectivity.